Deregulation of Adaptive T Cell Immunity in Multiple Myeloma: Insights Into Mechanisms and Therapeutic Opportunities - Leblay, Noémie; Maity, Ranjan; Hasan, Fajer; Neri, Paola (Frontiers in Oncology, 2020)
Immunotherapy has recently emerged as a promising therapeutic strategy for multiple myeloma (MM) patients. MM evolution is known to be associated with progressive immune dysregulation and loss of immune surveillance that fosters disease progression. Along with genetic changes in plasma cells, the bone marrow (BM) milieu creates a protective niche maintained by the complex interplay of BM stromal cells (BMSCs) and tumor cells that through bidirectional interactions and secretion of cytokines promote disease progression, drug resistance and facilitate immune escape. Local immune suppression and T-cell exhaustion are key mediators of clinical outcomes and responses to immunotherapy. Thus, further characterization of the immune defects present in MM is required to develop novel therapies and to repurpose the existing ones. This review seeks to provide insights into the mechanisms that promote tumor escape, cause inadequate T-cell stimulation and impaired cytotoxicity in MM. Furthermore, it highlights current immunotherapies being used to restore immune responses in MM and describes strategies being developed to circumvent these immune escape mechanisms.